Combination product of dermal matrix, human mesenchymal stem cells, and timolol promotes diabetic wound healing in mice. (28th July 2020) - Yang, Hsin-ya; Fierro, Fernando; So, Michelle; Yoon, Daniel J.; Nguyen, Alan Vu; Gallegos, Anthony; Bagood, Michelle D.; Rojo-Castro, Tomas; Alex, Alan; Stewart, Heather; Chigbrow, Marianne; Dasu, Mohan R.; et al.
Abstract: Diabetic foot ulcers are a major health care concern with limited effective therapies. Mesenchymal stem cell (MSC)-based therapies are promising treatment options due to their beneficial effects of immunomodulation, angiogenesis, and other paracrine effects. We investigated whether a bioengineered scaffold device containing hypoxia-preconditioned, allogeneic human MSCs combined with the beta-adrenergic antagonist timolol could improve impaired wound healing in diabetic mice. Different iterations were tested to optimize the primary wound outcome, which was percent of wound epithelialization. MSC preconditioned in 1 μM timolol at 1% oxygen (hypoxia) seeded at a density of 2.5 × 10 5 cells/cm 2 on Integra Matrix Wound Scaffold (MSC/T/H/S) applied to wounds and combined with daily topical timolol applications at 2.9 mM resulted in optimal wound epithelialization 65.6% (24.9% ± 13.0% with MSC/T/H/S vs 41.2% ± 20.1%, in control). Systemic absorption of timolol was below the HPLC limit of quantification, suggesting that with the 7-day treatment, accumulative steady-state timolol concentration is minimal. In the early inflammation stage of healing, the MSC/T/H/S treatment increased CCL2 expression, lowered the pro-inflammatory cytokines IL-1B and IL6 levels, decreased neutrophils by 44.8%, and shifted the macrophage ratio of M2/M1 to 1.9 in the wound, demonstrating an anti-inflammatory benefit. Importantly, expression of the endothelial marker CD31 was increased by 2.5-fold with this treatment. Overall, the combination device successfully improved wound healing and reduced the wound inflammatory response in the diabetic mouse model, suggesting that it could be translated to a therapy for patients with diabetic chronic wounds. : Abstract :